PERAN INFORMAL KELUARGA DALAM PENGENDALIAN KADAR GLUKOSA DARAH PADA PENDERITA DIABETES MELLITUS - Rosalina Rosalina (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2018)
Diabetes mellitus is a disease or disorder of chronic metabolism with multiethiology characterized by high blood sugar (hyperglycemia). Diabetes Mellitus can not be cured but can be controlled by regulating blood sugar levels. One important factor in controlling blood sugar levels is the role of the family To know the correlation between family's informal role and the control of blood glucose levels in people with diabetes mellitus at RSUD Ungaran Semarang Regency.The design of this study was descriptive correlational with cross sectional approach with the number of population of 176 people and samples of 64 respondents by using accidental sampling method. Data collection tools used questionnaires. Data analysis used SPSS version 23.0. Bivariate analysis was processed by using chi square test. The informal role of the family in people with diabetes mellitus is mostly in good category (75.0%). Control of blood glucose level in people with diabetes mellitus is mostly in good category (62,5%). There is significant correlation between family informal role and blood glucose control in patients with diabetes mellitus at RSUD Ungaran Semarang Regency, with p value 0,043 <0,05 (α). There is correlation between family's informal role and the control of blood glucose levels in people with diabetes mellitus at RSUD Ungaran Semarang Regency.We recommend that patients with DM further improve the control of blood glucose levels by increasing the role of the family so as to prevent the occurrence of complications